Eficacia de la fagoterapia en infecciones multirresistentes del pie diabético: revisión crítica de la literatura. - Barrios-Barbos, Katalina; López-Medina, Ralph Marien; Rodríguez-Panduro, Mauricio Humberto (Iatreia)
Introduction: Diabetes is a chronic metabolic disease that presents complications such as diabetic foot syndrome, expressed by ulcerations susceptible to infection by multidrug-resistant bacteria, making more difficult its treatment with conventional antibiotics and increasing the risk of amputation. Faced with this challenge, phage therapy is regarded as an alternative treatment for diabetic foot infection control. Objectives: To collect and analyze the available evidence about phage therapy efficacy in diabetic foot infection, to present its clinical potential and guide future research. Methods: A literature review was carried out in 11 databases, compiling 16 articles that evaluated efficacy, routes of administration, adverse events and treatment effects using individual phage therapy or combined with antibiotics. Results: The studies show positive treatment results, decreasing bacterial load and without reports of adverse effects. Efficacy changes depending on the complexity and presence of polymicrobial infections. Conclusions: The analysis of vitro and animal studies, as well as case reports, indicate positive results with phage therapy in multi-resistant diabetic foot infections, thereby finding a potential alternative to more invasive procedures such as amputation. However, large-scale controlled and randomized clinical trials are needed to obtain accurate data on its efficacy and safety.